Coping with the Influx : Service Delivery to Syrian Refugees and Hosts in Jordan, Lebanon, and Kurdistan, Iraq - Krishnan, Nandini; Russo Riva, Flavio; Sharma, Dhiraj; Vishwanath, Tara (World Bank, Washington, DC, 2020)
The Syrian crisis has led to rapid and large-scale population displacement. This paper uses several sources of data, including the United Nations Higher Commissioner for Refugees' registration database and multi-country, multi-topic surveys collected in 2015-16, to characterize service delivery in the context of a rapid influx of displaced populations. The study encompasses infrastructure services, such as electricity and garbage disposal, and social services, such as health and education, and considers both measures of access to services and their perceived quality.